cAMP-independent Crp homolog adds to the multi-layer regulatory network in Porphyromonas gingivalis - Śmiga, Michał; Roszkiewicz, Ewa; Ślęzak, Paulina; Tracz, Michał; Olczak, Teresa (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionPorphyromonas gingivalis encodes three CRP/FNR superfamily proteins: HcpR, PgRsp, and CrpPg, with CrpPg similar to cAMP-sensing proteins but not classified into known families. This study investigates the role of CrpPg in regulating the expression of factors essential for P. gingivalis virulence in A7436 and ATCC 33277 strains.MethodsThe role of CrpPg protein in P. gingivalis was determined using the ΔcrpPg mutant strains to characterize their phenotype and to assess the impact of crpPg inactivation on gene expression using RNA-seq and RT-qPCR. Additionally, the CrpPg protein was purified and characterized. ResultsKey findings in the ΔcrpPg mutant strain include up-regulated mfa1-5 and rgpA genes and down-regulated trxA, soxR, and ustA genes. While crpPg inactivation does not affect growth in liquid culture media, it impairs biofilm formation and enhances adhesion to and invasion of gingival keratinocytes. CrpPg binds directly to its own and mfa promoters without interacting with cyclic nucleotides or di-nucleotides. Its three-dimensional structure, resembling E. coli Crp in complex with cAMP and DNA, suggests that CrpPg functions as a global regulator independently of cAMP binding. The highest crpPg expression in the early exponential growth phase declines as cell density and metabolic conditions change over time, suggesting a regulatory function depending on the CrpPg protein amount.ConclusionsBy controlling the shift from planktonic to biofilm lifestyle, CrpPg may play a role in pathogenicity. Regulating the expression of virulence factors required for host cell invasion and intracellular replication, CrpPg may help P. gingivalis evade immune responses.